EGFR Exon 18 Mutations in Advanced Non-Small Cell Lung Cancer: A Real-World Study on Diverse Treatment Patterns and Clinical Outcomes - Xu, Haiyan; Yang, Guangjian; Li, Weihua; Li, Junling; Hao, Xuezhi; Xing, Puyuan; Yang, Yaning; Wang, Yan (Frontiers in Oncology, 2021)
Background Approximately 3–5% of patients with epidermal growth factor receptor (EGFR) mutation-positive non-small cell lung cancer (NSCLC) harbor exon 18 mutations. The appropriate treatment for such patients has not been clarified. The aim of this study was to investigate the response of patients with NSCLC harboring EGFR exon 18 mutations to different therapeutic options. Methods Between May 2014 and September 2020, the clinical outcomes of 82 patients harboring EGFR exon 18 mutations who received first-generation (1G) EGFR-tyrosine kinase inhibitor (TKI), second-generation (2G) EGFR-TKI afatinib, chemotherapy, and 1G TKI in combination with chemotherapy as the initial therapy were retrospectively analyzed. Results A total of 82 NSCLC patients harboring EGFR 18 mutations with whose treatment and survival outcomes were available were analyzed. The median age was 59 years, and 47 (57.3%) were female. The most common kind of EGFR exon 18 mutation was G719X (75.6%), followed by E709X (15.9%), E709_T710delinsD (3.6%), and other subtypes (4.9%). There was a significant difference in median progression-free survival (mPFS) by therapeutic strategy (P = 0.017). The mPFS of 1G TKI, 2G TKI afatinib, chemotherapy, and 1G TKI in combination with chemotherapy were 7.7 (95% CI, 4.2–11.2), 11.3 (95% CI, 5.6–17.0), 5.0 (95% CI, 2.3–17.7), and 11.1 (95% CI, 5.9–16.4) months, respectively. No significant difference in PFS was observed between afatinib and 1G TKI in combination with chemotherapy (P = 0.709). Conclusions Like afatinib, 1G TKI in combination with chemotherapy might be an effective treatment option for patients harboring EGFR exon 18 mutations.